SOME REMARKS ON IMAGINATION. NOTES ON THE MARGIN OF DE IMAGINATIONE BY GIANFRANCESCO PICO DELLA MIRANDOLA (1469-1533)1 - Wawrzonkowski, Krzysztof (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
The aim of this article is to explain the role of imagination in human life, as it was understood by Gianfrancesco Pico della Mirandola. First, I analyze the cognitive function of imagination. Then, I discuss its place within the intellectual powers, its misleading character, and its ability of causing emotions. Finally, I try to point at the ways of controlling it by reason and using it by man for their own purposes.